Choledocholithiasis in elderly patients with gallbladder in situ - is ERCP sufficient?. (2nd November 2018) - Sousa, Mafalda; Pinho, Rolando; Proença, Luísa; Rodrigues, Jaime; Silva, João; Gomes, Catarina; Carvalho, João
Abstract: Introduction: Along with increased life expectancy, the proportion of elderly patients with choledocholithiasis will increase and with this, the need for endoscopic cholangiopancreatography (ERCP). Current recommendations suggest laparoscopic cholecystectomy in all patients with choledocholithiasis to prevent biliary events. However, adherence to these recommendations is low, especially in older patients. Methods: Retrospective study that included non-cholecystectomized patients aged > =75 years who underwent ERCP for choledocholithiasis from 2013–2016 ( n  = 131). A new biliary event was defined as the need for a new ERCP, cholecystitis, cholangitis or gallstone pancreatitis. Aim: The aim of this study was to compare the outcomes of new biliary events and mortality in cholecystectomized vs non-cholecystectomized patients after ERCP. Results: Cholecystectomy was performed in 22% of the patients (92% laparoscopic). The post-cholecystectomy complication rate was 13% and the mortality rate was 7%. During the follow-up period (669 ± 487 days) a new biliary event occurred in 20% of patients - 10% new ERCP, 9% cholecystitis, 9% cholangitis and 2% pancreatitis. Cholecystectomized patients had fewer events (7% vs 24%, p  = .048) and longer time to event ( p  = .016). There was no statistically significant difference in all-cause mortality (14% vs 27%, p  = .13), mortality related to lithiasis (0% vs 9%, p  = .11) or time to mortality from all causes ( p  = .07) and related to biliary events ( p  = .07). Conclusions: In this group of elderly patients, cholecystectomy after ERCP prevented the occurrence of new biliary events but resulted in a non-statistically significant difference in mortality.